2022
DOI: 10.1186/s13567-022-01096-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of compliant, highly invasive, lipid A-altered, O-antigen-defected Salmonella strains as prospective vaccine delivery systems

Abstract: In the present study, two prospective Salmonella delivery strains, JOL2782 and JOL2837, were developed by gene deletions of lon and cpxR, which are related to cellular adhesion and intracellular survival. Additionally, sifA deletion was introduced for JOL2782, which confers immune susceptibility and improves antigen delivery. Similarly, the rfaL deletion and lpxE substitution for pagL were accomplished in JOL2837 to reduce virulence and endotoxicity. Thus, enhanced adhesion and invasion and reduced intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Therefore, it is essential for a live bacterial vaccine to reduce the endotoxic activity when the vaccine is injected. Our previous research indicated that the deletion of pagL , lpxR , and codon-optimized lpxE substitution for pagP to engineer Salmonella synthesizing 4′-monophosphoryl-hexa-acylated lipid A decreases the interaction of lipid A and TLR4 and enhances the ability of Salmonella to adapt to the host environment, and the Salmonella vaccine with monophosphorylated lipid A showed low endotoxic activity while maintaining its good immunogenicity [ 31 ], which was also demonstrated by recent research conducted by Lee groups [ 51 ]. Therefore, the lpxE gene was introduced into constructing S .…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, it is essential for a live bacterial vaccine to reduce the endotoxic activity when the vaccine is injected. Our previous research indicated that the deletion of pagL , lpxR , and codon-optimized lpxE substitution for pagP to engineer Salmonella synthesizing 4′-monophosphoryl-hexa-acylated lipid A decreases the interaction of lipid A and TLR4 and enhances the ability of Salmonella to adapt to the host environment, and the Salmonella vaccine with monophosphorylated lipid A showed low endotoxic activity while maintaining its good immunogenicity [ 31 ], which was also demonstrated by recent research conducted by Lee groups [ 51 ]. Therefore, the lpxE gene was introduced into constructing S .…”
Section: Discussionmentioning
confidence: 84%
“…With the innate ability of Salmonella to invade and proliferate in professional antigen-presenting cells (APCs), it has the advantage to directly deliver the DNA cargo to these cells and subsequently result in induction of cellular and humoral response [ 49 ]. Also, as safety concern is one of the important considerations in vaccine development especially with live-attenuated bacteria, of the vaccine delivery strain JOL2500 used in this study with genotype of Δlon, ΔcpxR, ΔsifA , and Δasd has been proven to have optimal survival in the host without any virulence [ 14 , 50 ]. Furthermore, vaccine production for this unique strategy can be easily scaled up and prepared rapidly at lower cost.…”
Section: Discussionmentioning
confidence: 99%
“…PCV2 causes several disease syndromes in pigs resulting in significant economic losses in the swine industry globally. In this study, the oral vaccination of the vaccine candidates elicited a broad spectrum of immunity, covering both systemic and mucosal sites through the safe and efficient vaccine delivery of the Salmonella vaccine strain to different organs such as liver, spleen, and lungs [ 29 , 35 , 36 ] and expression of the target antigens, Cap and Rep, in antigen-presenting cells ( Figure 2 ). Salmonella Typhimurium is one of several bacterial species that can transfer eukaryotic expression plasmids into host cells, which can serve as a carrier for vaccine antigens or its genetic material [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…To diminish the impact of pre-existing immunity on the vaccine delivery efficiency and immunogenicity, an attenuated Salmonella vector strain was previously engineered by deleting the O-antigen ligase ( rfal ) from the Salmonella Typhimurium genome [ 70 ]. The optimized Salmonella vaccine strain JOL3000 with genotype Δlon, Δcpxr, Δrfal, ΔpagL::lpxE, Δasd [ 36 , 71 ] can be utilized for further studies to explore its efficient vaccine delivery by overcoming the pre-existing antibodies to Salmonella and potential application in the swine model. Aside from this, optimizing the dosage, vaccination schedule, and incorporation of stimulators for the host immune response could also be explored to further improve its immunogenicity.…”
Section: Discussionmentioning
confidence: 99%